Komparasi Kinerja Keuangan: BSI vs Mandiri Pasca-Merger Menggunakan Metode CAMEL (2021-2023) - Andi Idwar Sefatnatse (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2026)
This comparative study aims to comprehensively evaluate the financial performance comparison between PT Bank Syariah Indonesia Tbk and PT Bank Mandiri Tbk post-merger during the economic recovery period from 2021 to 2023. The background is based on the urgency to measure merger impacts towards banking operational efficiency levels. The analysis applies financial ratios using the CAMEL model framework which encompasses Capital, Asset, Management, Earnings, and Liquidity. The quantitative comparative methodology was implemented through parametric testing, namely the Independent Sample T-Test, and non-parametric testing via the Mann-Whitney U Test. Research samples utilized quarterly published secondary financial reports data observations at a five percent significance level. Empirical testing results prove BSI has fundamental resilience equivalent to conventional banks. This objective fact is evident from the absence of statistically significant differences in capital adequacy indicators or Capital Adequacy Ratio and asset quality represented by Non-Performing Financing. Conversely, regarding management efficiency through Net Profit Margin, Return on Assets profitability, and Financing to Deposit Ratio liquidity, Bank Mandiri demonstrates absolute dominance with a highly significant performance gap. This distinct difference is primarily triggered by the heavy post-merger transitional burden borne by BSI initially. In conclusion, although BSI has successfully established a very solid capital structure, the acceleration of operational efficiency optimization and liquidity strategy refinement are crucial actions requiring immediate realization. Research implications strongly recommend the continuous expansion of digital service transformation to systematically boost revenue generation, ensuring its profitability can fiercely compete against giant national conventional banks moving forward into the long term future